Role of kidney biomarkers of chronic kidney disease: An update - Khan, Zeba (2014)
Chronic kidney disease (CKD) is a progressive pathological condition marked by deteriorating renal function over time. Diagnostic of kidney disease depend on serum creatinine level and glomerular filtration rate which is detectable when kidney function become half. The detection of kidney damage in an early stage needs robust biomarkers. Biomarkers allow monitoring the disease progression at initial stages of disease. On the onset of impairment in cellular organization there is perturbation in signaling molecules which are either up-regulated or down-regulated and act as an indicator or biomarker of diseased stage. This review compiled the cell signaling of different kidney biomarkers associated with the onset of chronic kidney diseases. Delay in diagnosis of CKD will cause deterioration of nephron function which leads to End stage renal disease and at that point patients require dialysis or kidney transplant. Detailed information on the complex network in signaling pathway leading to a coordinated pattern of gene expression and regulation in CKD will undoubtedly provide important clues to develop novel prognostic and therapeutic strategies for CKD.